Uniqueness of Solution of the Initial Value Problem for ut=ΔUm-up (Journal of Partial Differential Equations, 1991)
The uniqueness of solution of the Cauchy problem u_t = Δu^m - u^p, \qquad S_T = R^n × (0, T) u(x, 0) = Φ(x), \qquad × ∈ R^n is obtained. Where n ≥ 1, m, p > 0, Φ(x) ∈ L^∞(R^n), Φ(x) ≥ 0.
Keywords: Uniqueness of solution; initial value problem